Thrombophilia screening in young patients with cryptogenic stroke - Haeusler, K. G.; Herm, J.; Hoppe, B.; Kasabov, R.; Malzahn, U.; Endres, M.; Koscielny, J.; Jungehulsing, G. J. (Hämostaseologie, 2012)
The clinical relevance of thrombophilia screening in stroke patients is still a matter of debate, and descriptions of larger patterns of genetic variability are rare. We assessed the frequency of hereditary hypercoagulability in young patients with cryptogenic stroke (n = 44) and in healthy blood donors (n = 282) without prior cardiovascular event. Furthermore, we focused on the impact of thrombophilia screening on secondary stroke prevention. Results: Compared to the control group (19–67 years; median 38.5 years; 64% women), there was a lower prevalence of the FVII-R353Q mutation (p = 0.033) in stroke patients (17–52 years; median 36 years; 59.1% women). Of note, the FVII-R353Q mutation lowers FVII plasma levels, probably reducing the risk of cardiovascular events. The prevalence of the remaining 13 gene polymorphisms did not differ significantly. However, the prevalence of FV Leiden mutation tended to be higher among stroke patients. Conclusion: Overall, extended screening for inherited thrombophilia had an impact on medical stroke prevention in every sixth patient with cryptogenic stroke.
Keywords: Ischaemic stroke; secondary stroke prevention; FVII-R353Q mutation; genetics